FEMINIST RESEARCH METHODOLOGIES IN LAW - Maria da Silva, Salete (Revista Gênero e Interdisciplinaridade, 2025)
With this text, I intend to contribute to a better connection between the scientific legal community, especially undergraduate and graduate law students, and feminist contributions to research methodologies and their potential uses in the legal field.